The sequential mediating roles of alexithymia and interpersonal problems in the relationship between autistic traits and suicidal ideation: evidence from Chinese college students - Li, Sheliang; Wang, Wan (Frontiers in Public Health, 2025)
BackgroundAlthough prior studies suggested that higher levels of autistic traits correlated with more suicidal thoughts and behavior, the specific underlying mechanism was not clear. The present study was designed to expand prior findings and test the mediating roles of alexithymia and interpersonal problems on the relation between autistic traits and suicidal ideation among large population-based college samples.MethodsA total of 6,763 college students (including 3,829 females) completed Autism-Spectrum Quotient, Toronto alexithymia Scale-20, Chinese Adolescents Self-Rating Life Events Checklist and Symptom Checklist.Results1.54% college students reported high autistic traits and 9.54% college students had suicidal ideation. Autistic traits were positively correlated with suicidal ideation. The sequential mediating effects of alexithymia and interpersonal problems on the relation between autistic traits and suicidal ideation were significant.ConclusionThese findings contribute to our further understanding of how autistic traits affect suicidal ideation in the context of complex risks and outcomes. They are also helpful in the prevention and treatment of suicidal ideation and behaviors.